Novel Absorber Material Design Based on Thiazole Derivatives Using DFT/TD-DFT Calculation Methods for High-Performance Dye Sensitized Solar Cell - Nurrosyid, Naufan; Fahri, Mirad; Apriliyanto, Yusuf Bramastya; Basuki, Rahmat (Indonesian Scholar Society, 2022)
Thiazole derivative molecules with a low energy gap have been successfully designed using the DFT/TD-DFT calculation methods. The calculations were simulated by adding varied numbers of thiophenes (1, 2, 3, and 10) and electron donating molecules of –H, -NH2, -OCH3, and –COOH in the ethanol solvent. The best thiazole derivative was the molecule constructed using a long-conjugated bridge of 10-thiophenes, the carboxyl anchoring site, and an amine addition as the electron donating molecule with an energy gap of 1.66 eV and a strong UV-Vis absorption in the red light region (673.20 nm). These designed molecules are beneficial to be applied in the equator area such as Indonesia. Further, the profound effects of the thiophene bridge in terms of the structural and energy gaps, and the variation of electron-donating molecules affected the photonic properties have been demonstrated in this paper.